What Helps and What Hinders in Cross-Cultural Clinical Supervision: A Critical Incident Study. (January 2013) - Wong, Lilian C. J.; Wong, Paul T. P.; Ishiyama, F. Ishu
This study investigated what helped and what hindered in cross-cultural supervision. The participants were 25 visible minority graduate students and early counseling professionals. They were individually interviewed according to an expanded version of Flanagan's critical incident technique. The most frequently cited positive themes were subsumed in five key areas: (a) personal attributes of the supervisor, (b) supervision competencies, (c) mentoring, (d) relationship, and (e) multicultural supervision competencies. The most frequently reported negative themes were grouped into five areas: (a) personal difficulties as a visible minority, (b) negative personal attributes of the supervisor, (c) lack of a safe and trusting relationship, (d) lack of multicultural supervision competencies, and (e) lack of supervision competencies. The results support a person-centered mentoring model of effective supervision.